Improving glycemic control by transitioning from the MiniMedTM 640G to 770G in Japanese adults with type 1 diabetes mellitus: a prospective, single-center, observational study - Satoshi Kubota; Ai Sato; Manami Hosokawa; Yosuke Okubo; Shohei Takayama; Atsuko Kaneko; Yasuho Shimada; Yuki Asano; Yoshihiko Sato; Masanori Yamazaki; Mitsuhisa Komatsu (Endocrine Journal)
The effectiveness of a hybrid closed-loop (HCL) system in improving glycemic control is unclear in Japanese individuals. Therefore, we assessed the effect impact of the MiniMed 770G HCL system on glycemic control in this population. This prospective, single-center, 24-week observational study (registration number: UMIN000047394) enrolled 23 individuals with type 1 diabetes mellitus using the Medtronic MiniMed 640G system. The primary endpoint was the improvement in time in the range of 70–180 mg/dL after transitioning to the MiniMed 770G HCL system. We observed an increase in time in range (from 64.1 [55.8–69.5] to 70.9 [67.1–74.4] %, interquartile range 25–75%, p < 0.001) and a decrease in glycated hemoglobin level (from 7.4 [7.0–7.9] to 7.1 [6.8–7.4] %, p = 0.003). There was a significant reduction in time above the range (181–250 mg/dL: 25.8 [20.9–28.6] to 19.5 [17.1–22.1] %, p < 0.001; >251 mg/dL: 8.7 [4.0–13.0] to 4.7 [3.6–9.1] %, p < 0.001). Time below the range remained unchanged (54–69 mg/dL: 1.8 [0.4–2.4] to 2.1 [0.4–3.9] %, p = 0.24; <54 mg/dL: 0.2 [0.0–1.0] to 0.5 [0.1–1.3] %, p = 0.14). In a subgroup of 12 patients with a high HCL implementation rate, the basal insulin infusion decreased immediately after mealtime insulin administration and increased after approximately 120 minutes. The ratings from questionnaires assessing treatment burden, satisfaction, and quality of life remained unchanged. The MiniMed 770G HCL system improved glycemic control and optimized insulin delivery, particularly in patients with high implementation rates.